Seasonal variation of apparent male fertility and 2n pollen production in plantain and banana - Ortíz, R.; Ulburghs, F.; Okoro, J. (1998)
Current efforts to produce improved genotypes of plantain (Musa spp. AAB genomic group) and banana (Musa spp. AAA genomic group) depend on identifying triploid, female-fertile clones and crossing them with male-fertile, diploid wild or cultivated accessions. Apparent male fertility, as measured by pollen stainability, and production of 2n pollen (gamete with the sporophytic chromosome number) were examined over a period of 1 year (Oct. 1992 to Oct. 1993) in `Calcutta 4' (wild banana), `Galeo', and `Pisang lilin' (cultivated bananas), and in TMP2x 1297-3 (plantain—banana hybrid), which are the most popular diploid parents in the breeding program of the International Institute of Tropical Agriculture. Differences in pollen stainability were found among these clones. However, a seasonal variation in pollen stainability was observed in all clones except `Calcutta 4'. Solar radiation was positively associated (P < 0.05) with pollen stainability. Pollen stainability in the diploid banana parents was compared with seed set after triploid-diploid crosses between plantains and bananas. There was a clear difference in the capacity of male parents to fertilize, but seed set was not significantly correlated with pollen stainability (r = 0.246, P = 0.358). Although the seasonal maximum seed set coincided with the time of maximum pollen stainability, variation in seed set seems to be due mainly to seasonal variation in female fertility. Of all clones examined, only `Pisang lilin' produced 2n pollen throughout the year. Seasonal variation in 2n pollen production was highly correlated (P < 0.05) with solar radiation, temperature, total pan evaporation, rainfall, and minimum relative humidity. The identification of male-fertile 2n pollen-producing diploid accessions, and of the best time of the year to maximize fertility and 2n pollen production, will allow the synthesis of polyploid Musa hybrids through sexual polyploidization.